2019
DOI: 10.1590/1414-431x20198525
|View full text |Cite|
|
Sign up to set email alerts
|

[RETRACTED ARTICLE] Ginsenoside Rd inhibits IL-1β-induced inflammation and degradation of intervertebral disc chondrocytes by increasing IL1RAP ubiquitination

Abstract: Many compounds of ginsenosides show anti-inflammatory properties. However, their anti-inflammatory effects in intervertebral chondrocytes in the presence of inflammatory factors have never been shown. Increased levels of pro-inflammatory cytokines are generally associated with the degradation and death of chondrocytes; therefore, finding an effective and nontoxic substance that attenuates the inflammation is worthwhile. In this study, chondrocytes were isolated from the nucleus pulposus tissues, and the cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(28 reference statements)
1
2
0
Order By: Relevance
“…Consistently, cell positivity of COX2 also increases in more degenerative NP when compared to NP at lower degenerative grades. We further checked the expression of COX2 in cell culture in vitro and found that IL-1 β treatment could upregulate COX2 expression in human NP cells, which is consistent with other findings [ 34 , 47 ]. This indicates that COX2 is involved in the IL-1 β -induced inflammatory process.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Consistently, cell positivity of COX2 also increases in more degenerative NP when compared to NP at lower degenerative grades. We further checked the expression of COX2 in cell culture in vitro and found that IL-1 β treatment could upregulate COX2 expression in human NP cells, which is consistent with other findings [ 34 , 47 ]. This indicates that COX2 is involved in the IL-1 β -induced inflammatory process.…”
Section: Discussionsupporting
confidence: 89%
“…In rat [ 45 ] and dog [ 46 ] models with induced IVD degeneration, increased expression of COX2 has been found in degenerated discs. In disc cell culture, IL-1 β [ 34 , 47 ] and TNF- α [ 48 ] have been found to elevate inflammatory gene expression including COX2. However, the information about COX2 expression in native human IVD at different degeneration grades is still scarce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation